Evaluación e implementación de la inseminación artificial por laparoscopia en dos unidades de producción ovina semi-intensivas del Estado de Michoacán - Olivo Zepeda, Ingrid Brenda (Universidad Michoacana de San Nicolás de Hidalgo, 2015)
In Mexico, artificial insemination (AI) is rarely used in sheep herds. The objective of this work was to implement and evaluate the laparoscopic artificial insemination technique in two semi-intensive sheep production units in the state of Michoacán. The tests were carried out in summer. In the first trial, 20 females were synchronized, of which 12 were inseminated by laparoscopy and 8 with natural breeding. In trial 2, 21 females were synchronized, of which 10 were artificially inseminated and 11 were served by natural breeding. Oral Melengestrol Acetate (MGA) was used in both tests for the synchronization of heats in sheep (0.22mg / female / 17 days). The detection of estrus was carried out every eight hours, using two males with aprons. The ewes were inseminated between 12-18 hours after heat detection; frozen semen was used in the first test and refrigerated semen at 5 ° C in the second. Two 0.25 ml straws were used for each sheep (100x106). The pregnancy diagnosis was made by ultrasound at 45 days. In both trials, 42 (100%) females presented estrus, between days 4-8 post-treatment with MGA. In the case of the trial, the gestation percentage for natural mounting and artificial insemination was 50% and 83.3%, respectively, without statistical differences (P> 0.05). In trial 2 (The pregnancy percentage for natural mounting and artificial insemination was 45.5% and 50.0%, respectively, without statistical differences (P> 0.01). It was detected in one trial that the body condition and weight of the female at the time of service, they affected the pregnancy rate. No effects of the stallion or the time of insemination were observed. The cost of AI was higher than natural breeding, but without considering its potential in genetic improvement.

En México, la inseminación artificial (IA) se utiliza poco en hatos ovinos. El objetivo de este trabajo fue implementar y evaluar la técnica de inseminación artificial por laparoscopia en dos unidades de producción ovina semiintensivas en el estado de Michoacán. Los ensayos se realizaron en verano. En el primer ensayo, se sincronizaron 20 hembras, de las cuales 12 se inseminaron por laparoscopía y 8 con monta natural. En el ensayo 2 se sincronizaron 21 hembras de las cuales 10 se inseminaron artificialmente y 11 fueron servidas por monta natural. En ambos ensayos para la sincronización de calores de las ovejas se utilizó Acetato de Melengestrol (MGA) por vía oral (0.22mg /hembra/17 días). La detección de estros se realizó cada ocho horas, utilizando dos machos con mandil. Las ovejas se inseminaron entre las 12-18 horas después de detectado el celo; en el primer ensayo se empleó semen congelado y en el segundo semen refrigerado a 5°C. Se utilizaron dos pajillas de 0.25 ml para cada oveja (100x106). El diagnóstico de gestación se realizó por ecografía a los 45 días. En ambos ensayos 42 (100%) hembras presentaron estro, entre los días 4-8 postratamiento con MGA. En el caso del ensayo El porcentaje de gestación para monta natural e inseminación artificial fue del 50% y 83.3%, respectivamente, sin diferencias estadísticas (P>0.05),. En el ensayo 2 (El porcentaje de gestación para monta natural e inseminación artificial fue del 45.5% y 50.0%, respectivamente, sin diferencias estadísticas (P>0.01). Se detectó en un ensayo, que la condición corporal y el peso de la hembra al momento del servicio afectaron la tasa de preñez. No se observaron efectos del semental ni del momento de la inseminación. El costo de la IA fue mayor que la monta natural, pero sin considerar su potencial en el mejoramiento genético.
Facultad de Medicina Veterinaria y Zootecnia. Maestría en Desarrollo Tecnológico en Sistemas de Producción Animal
Keywords: info:eu-repo/classification/cti/6; FMVZ-M-2015-2293; Inseminación artificial; Laparoscopia; Fertilidad en ovinos; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/5688